Case Report: Primary small bowel adenocarcinoma with peritoneal metastasis responded well to a CapeOX + bevacizumab regimen - Fu, Guang; Tang, Zhen; Xu, Zishun; Zhang, Shao (Frontiers in Gastroenterology, 2023)
Background Small bowel adenocarcinoma (SBA) is a rare condition often presenting with various non-specific gastrointestinal symptoms, making its diagnosis challenging. Delayed diagnosis is common, as patients may not receive the correct diagnosis until complications arise, necessitating further investigations. Furthermore, the management of SBA patients poses difficulties due to the scarcity of high-quality evidence. Case presentation In this report, we present the case of an elderly man with SBA in the ileum who arrived at our emergency room with acute abdominal pain. The diagnosis was not made until the SBA caused a perforation, leading to acute abdominal pain. An emergent exploratory laparotomy revealed a 3 cm × 3 cm perforated tumor in the ileum, along with widespread metastatic nodules on the omentum, ascending colon, descending colon, and rectum. Postoperative pathological evaluation confirmed the diagnosis of SBA with peritoneal metastasis (pT4N2M1, stage IV). Following surgery, the patient received palliative systemic chemotherapy, which included the CapeOX regimen and the anti-VEGF monoclonal antibody bevacizumab. Remarkably, the patient responded well to this therapy, displaying good tolerance, and we observed no signs of disease progression. As of now, the patient is in good health and continuing with regular follow-up. Conclusion The early diagnosis of small bowel adenocarcinoma remains a challenge. Delayed diagnosis can lead to a poor prognosis, underscoring the importance of considering SBA as a potential diagnosis for patients with unexplained abdominal pain and gastrointestinal symptoms. This case also highlights the efficacy of palliative chemotherapy with the CapeOX regimen combined with bevacizumab in controlling SBA.